Analisis penerapan ekonomi islam dalam prespektif generasi millenial muslim - tsaniyah, ainin (Maliki Interdisciplinary Journal, 2025)
The implementation of the economy in Indonesia is developing increasingly rapidly with increasing technological tools. With this, the Muslim millennial generation must take part in controlling and implementing the economy. Because it can be seen that in the near future, misuse of technology, such as online loans, is not uncommon in the current era. Pinjol is prohibited if it contains an element of usury (price interest) because in the Qur’an itself the prohibition of usury is explained. Therefore, I conducted research from several sources to determine and minimize the application of usury in society. Namely by introducing good and correct Islamic economic values ​​to society. So it is hoped that the mini Muslim millennial generation can take part in expanding understanding of the application of economic.